Atypical Neurological Manifestation in Childhood Microscopic Polyangiitis: A Case Report and Review of Literature - Suksai, Preawkalaya; Wasuanankun, Suphawe; Lekhavat, Vitit; Sirimongkolchaiyakul, Ornatcha; Tangcheewinsirikul, Sirikarn (Frontiers in Pediatrics, 2022)
Abstract Microscopic polyangiitis (MPA), a systemic necrotizing vasculitis of small vessels, is primarily associated with necrotizing and crescentic glomerulonephritis and pulmonary capillaritis. Neurological involvement, particularly of the central nervous system (CNS), is scarcely observed. Case report Herein we report the case of a 13-year-old Thai girl diagnosed with MPA presented with rapidly progressive glomerulonephritis (RPGN). Renal biopsy was performed demonstrated crescentic glomerulonephritis with negative immunofluorescence and positive titer of myeloperoxidase antibody. Pulse methylprednisolone (MP) and cyclophosphamide (CYC) as well as plasmapheresis were initiated. During the follow-up period, she experienced a brief generalized tonic–clonic seizure. The potentially differential diagnosis of new-onset neurological manifestation contains infection owing to the immunocompromised status of the patient and CNS vasculitis as a result of the disease itself. Investigation was done and contrast magnetic resonance imaging studies of the brain showed multifocal patchy T2/FLAIR-hyperintense lesions in the cerebral as well as cerebellum regions, and irregular narrowing along the V4 segment of the right vertebral artery was demonstrated in magnetic resonance angiography. In the presence of CNS vasculitis, pulse MP and CYC were provided. Symptom of nervous system improved gradually. Conclusion In our case with MPA revealed RPGN with neurological manifestation. Despite being scarcely reported, CNS vasculitis is organ threatening, and the involvement of multidisciplinary care teams with prompt management are highly advisable.